Management of patients on anticoagulant therapy undergoing dental extractions: a systematic review - Oliva-Mella, Patricio; Ruiz-Gutiérrez, Maria Francisca (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: the management of patients who have undergone dental surgeries and are on antithrombotic therapy is debatable. The goal of this study was to establish the management of patients on anticoagulant therapy prior to dental extractions. Methods: this was a systematic review based on the search for scientific randomized controlled studies (clinical trials). Articles were searched in databases such as Embase, Pubmed, or Ebsco, selecting the articles that met the inclusion criteria and correlated dental extractions to the use of anticoagulant therapy. Results: 5 studies were found with a total of 548 patients, 282 of which had their anticoagulant therapy modified and the remaining 266 kept their therapy prior to extractions. The number of events (hemorrhages) was measured in both groups, observing that most events occurred in the group of patients whose therapy was modified (35 events) while there were 18 cases in patients who kept their therapy. Heterogeneity in this study was null (I² = 0%, p = 0.99). Conclusion: there are no significant differences in the hemorrhage levels of patients who maintain anticoagulant therapy compared with those who had their therapy modified prior to dental extractions. It is then recommended to keep the treatment.